2010
DOI: 10.1016/j.socscimed.2009.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Job insecurity and health: A study of 16 European countries

Abstract: Although the number of insecure jobs has increased considerably over the recent decades, relatively little is known about the health consequences of job insecurity, their international pattern, and factors that may modify them. In this paper, we investigated the association between job insecurity and self-rated health, and whether the relationship differs by country or individual-level characteristics. Cross-sectional data from 3 population-based studies on job insecurity, self-rated health, demographic, socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
157
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(175 citation statements)
references
References 31 publications
12
157
0
6
Order By: Relevance
“…Organizations change rapidly and employees need to learn new skills and gain new knowledge in order to keep their jobs [43]. A study encompassing 16 European countries showed that job insecurity is connected with poor health, regardless of age, sex, education or economic status [44]. Polish and Slovakian nurses reported concern about their IJOMEH 2013;26(4) 596 The questionnaires were completed anonymously and submitted directly to the researcher.…”
Section: Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…Organizations change rapidly and employees need to learn new skills and gain new knowledge in order to keep their jobs [43]. A study encompassing 16 European countries showed that job insecurity is connected with poor health, regardless of age, sex, education or economic status [44]. Polish and Slovakian nurses reported concern about their IJOMEH 2013;26(4) 596 The questionnaires were completed anonymously and submitted directly to the researcher.…”
Section: Objectivementioning
confidence: 99%
“…Moreover, in this study emotional exhaustion correlated with job security (see Table 1). According to Laszlo's results [44], this can help anticipate the health costs of the process of energy depletion. Insufficient respect and esteem also had an influence (although weaker) on the intensification of emotional exhaustion in surgical nurses.…”
Section: Ijomeh 2013;26(4)mentioning
confidence: 99%
“…There are also related studies (e.g. Vahtera et al 1997;Martikainen et al 2008;László et al 2010;Rugulies et al 2010) that examine the effects of downsizing, job insecurity and workplace closures on health and mortality.…”
Section: Data and Variablesmentioning
confidence: 99%
“…In another recent study it has been shown that across 16 European countries there is a robust statistical association between insecurity and poor health among older employees [4]. The study finds that employees who reported that their "job security was poor" were 39% less likely to report that their health was good or very good (as opposed to fair, poor, or very poor).…”
Section: Empirical Evidence Linking Insecurity To Types Of Ill-healthmentioning
confidence: 88%